Penyelesian Sengketa Jual Beli Tanah Dibawah Tangan Antara Pembeli Dengan Ahli Waris Secara Litigasi Sebagai Jalan Mendapatkan Kepastian Hukum - Soewita, Samuel; Mahendra, Reza (Pamulang Law Review, 2024)
Land disputes never subside, and in fact tend to continue to increase in both intensity and completeness, as access to obtain and own land becomes increasingly difficult. Disputed land issues include land objects, boundaries, area, land status, subject surroundings, rights containing, transfer of rights and so on. One way to resolve land disputes is generally through the courts (litigation). This route is used if the parties feel that their rights have been disturbed and have caused harm, then the person who feels their rights have been harmed can file a lawsuit in court in accordance with applicable procedures. A lawsuit before the court always contains elements of a plaintiff or plaintiffs, a defendant and a co-defendant or co-defendants. The method of settlement through the court is regulated in the Civil Procedure Law (Burgerlijk Procesrecht, Civil Law of Procedure). It is hoped that with the existence of civil procedural law, parties to a dispute can restore their rights that have been harmed by other parties through a court that provides a sense of legal certainty.